Task-Oriented Plyometric Intervention for Augmenting Upper Extremity Strength and Function in Hemiparetic Cerebral Palsy: A Randomized Controlled Trial. - Elnaggar, Ragab K; Ramirez-Campillo, Rodrigo; Elfakharany, Mahmoud S; Alrawaili, Saud M; Alghadier, Mshari; Alotaibi, Mazyad A; El-Basatiny, Heba MY; Elsaeed, Tamer M (NeuroRehabilitation, 2026)
Background: Children with hemiparetic cerebral palsy (Hemi-CP) often face challenges in strength and function, limiting participation in daily activities. While plyometric exercise (Plyo-Ex) has shown promise in improving neuromuscular performance in other populations, its applications in pediatric neurorehabilitation remains understudies. Objective: To assess whether a 12-week Plyo-Ex program could elicit meaningful improvement in muscle strength and upper extremity function in children with Hemi-CP. Methods: A prospective, randomized controlled trial involving 58 children with Hemi-CP was conducted. Participants were assigned to either a Plyo-Ex group or a control group receiving standard exercise approaches. The Plyo-Ex group completed supervised upper-extremity-oriented Ply-o-Ex program (∼45 min, twice weekly for 12 weeks), with at least 48 h between sessions. Measurements at the baseline and post-treatment included muscle strength (shoulder flexors, external rotators, abductors, elbow extensors, and wrist extensors), unilateral upper extremity function (movement quality, spontaneity, dynamic segmental alignment, and grasp-release capability), and bimanual hand function. Results: Compared to the control group, the Plyo-Ex group demonstrated significant moderate-to-large increases in muscle strength across all tested muscle (all P < 0.05; η 2p = 0.07–0.18). Improvements were also seen in unilateral upper extremity function [quality of function (P = 0.006, η 2p = 0.13), spontaneity (P = 0.003, η 2p = 0.14), dynamic segmental alignment (P = 0.018, η 2p = 0.10), and grasp-release capability (P = 0.033, η 2p = 0.08)] as well as the bimanual hand function (P = 0.004, η 2p = 0.14). Conclusions: Evidence from this trial indicates that Plyo-Ex may serve as a viable intervention to enhance upper extremity strength and function in children with Hemi-CP. Rehabilitation professionals may consider adopting this modality as part of a comprehensive, evidence-based therapeutic plan. Trial Registration: ClinicalTrial.gov (Identifier: NCT06980246)